Efektivitas Metode Imlā’ Manẓūr dalam Meningkatkan Keterampilan Menulis Bahasa Arab Siswa Madrasah Tsanawiyah - Susanti Susanti; Syamsuddin Asyrofi (Study Program of Arabic Language Teaching, 2020)
The lack of use the writing skills method raises several obstacles experienced by students, including weaknesses in understanding the basics of Arabic writing and difficulty in answering Arabic questions. Therefore, it is necessary to improve learning as an effort to improve writing skills by applying the imla’ manzur method. This research is an experimental study with a pretest-posttest control group design model, aimed at finding out the effectiveness of the imla’ manzur method. Data collection techniques in this study used observation, tests, questionnaires, interviews, and documentation. Then the validity of the data is tested using the independent sample t-test. The results obtained were that in the experimental class the mastery of Arabic writing skills of students after applying the imla’ manzur method had increased the average value from 52.08 to 78.57. Then, the results of the independent sample t-test showed a significant difference in the mastery of Arabic writing skills in the experimental class and the control class 0.000 < 0.05 after treatment, so that the conclusion of this study based on the data obtained showed that the application of the imla’ manzur method was effective in improving students Arabic writing skills. Evidenced by a significant increase in learning outcomes, student enthusiasm when taking turns to write vocabulary and sentences in Arabic on the board, as well as growing sensitivity of student analysis of Arabic writing skills.